Mixed matrix membranes based on polysulfone and rice husk extracted silica for CO2 separation - Waheed, N. (Elsevier B.V., 2016)
Mesoporous silica particles after extraction from rice husk ash were used as fillers in polysulfone based mixed-matrix membranes (MMMs). The fillers were functionalized with 4-aminophenazone (4-AMP) to enhance the CO2-philic properties. The attractive feature of this research was the utility of extracted silica from a biological waste-the rice husk ash. A good dispersion and adhesion of the filler within the polymer matrix were confirmed by the gas permeation results, SEM images and FTIR analysis. The results revealed that all MMMs showed high permeabilities in comparison to pristine polysulfone membrane. The higher gas permeabilities were attributed to the presence of large mesopores in the filler that led to faster diffusion of the penetrant gas. The functionalized silica showed significantly higher CO2/CH4 and CO2/N2 selectivities. The highest ideal selectivities obtained for CO2/N2 and CO2/CH4 at a maximum of 40 filler loading, were 32.79 and 33.31 respectively. All synthesized membranes were tested at various operating temperatures and their activation energies were also calculated. The highly ordered structures with short and straight pore channels and improved gas permeation properties warrant the silica extracted from rice husk as promising filler for industrial gas separation under varying conditions of temperature. Â© 2016 Elsevier B.V.